Determination of the antibacterial, antioxidant activity, isolation and characterisation of active compounds from the leaves of Rhys Leptodictia plant - Matamela, Tshifhiwa (My University, 2014)
Rhus leptodictya commonly known as a mountain karee belongs to the family Anacadeceae and has been used since antiquity in tradition medicine. In the present study antimicrobial and antioxidant potentials of the leaves of Rhus leptodictya were studied, followed by isolation of at least one active compound which showed antibacterial and antioxidant potentials. Extractions were performed based on the polarity of the solvent used. The solvents used were hexane, dichloromethane, ethyl acetate, acetone and methanol. Dichloromethane was found to be extracting more compounds than the other used solvents. Thin layer chromatography (TLC) was used to determine the chemical composition of the extracts by employing different solvent systems. The results showed that, of the solvent systems used, namely ethyl acetate: methanol: water (EMW) 40: 5: 1; chloroform: ethyl acetate: formic acid (CEF) 5: 4: 1 and benzene: ethanol: ammonium hydroxide (BEA) 90:10:1, BEA produced better separations. To determine the antioxidant potential of the leaves, 2.2-diphenyl picrylhydrazyl (DPPH) was used. Different spot with different Rf values were found to be active by show of yellow colour on the TLC plate. The yellow colour is due to the proton gained by DPPH when it reacts with active compound. Bioutography results showed that different leaves were active against selected bacterium. Minimum inhibitory concentration studies showed that the methanol extract was more active against B.subtilis and S.pnuemonia at concentration less than 0.1 mg/ml respectively. Dichloromethane extract was found to be the least effective on S.pneumonia, as compared to the methanol, acetone and ethyl acetate extracts. In terms of the total activity, the ethyl acetate concentration showed better total activity than the other extracts studied in this research. A new compound 7, 8-trihydroxy-2-(4’hydroxy phenyl)-3-5-[5’’, 6’’-dihydroxy-2’’-O-(4’’’hydroxyphenyl)-4-1t-chromen-4’’-one]-41t-chromen-4-one was isolated and characterized by H1-NMR, C13-NMR, MS and IR. According to the literature search, this compound has never been isolated from any plant and it has showed both antioxidant and antibacterial activity.
M Tech. (Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Rhus leptodictya; Mountain karee; Medicinal properties of plants; 615.321; Medicinal plants -- South Africa.